PENGARUH GUIDED IMAGERY TERHADAP CEMAS DAN NYERI PADA PASIEN CHOLELITIASIS DI RUMAH SAKIT - Fitriyati, Yayat; Susanto, Wigyo; Rochmawati, Dwi Heppy (Yayasan Healing and Healthcare Education, 2026)
Cholelithiasis patients experience gallstone obstruction which causes the patient to feel pain in the abdomen, the pain makes the patient feel anxious to do activities or mobilization. Anxiety and pain can be overcome with non-pharmacological measures, one of which is guided imagery therapy. Guided imagery relaxation techniques can be used to restore hormonal balance in the body after experiencing disorders, making the body feel more relaxed overall. Objective: This study aims to determine the effect of guided imagery on anxiety levels and pain scales in cholelithiasis patients at Sari Asih Hospital. Method: A quasi-experimental study with a pre-experiment one group pre-post test design involving 35 cholelithiasis patients at Sari Asih Hospital was taken using consecutive sampling techniques. Data were analyzed univariately and bivariately using the chi square test. Results: The results of the univariate analysis showed that before the intervention the majority of anxiety was severe (71.4%) and pain was moderate (62.9%), while, after the intervention the majority of anxiety was mild (51.4%) and pain was mild (62.9%). Bivariate analysis results showed an effect of guided imagery on anxiety (p=0.000) and pain (p=0.000) in cholelithiasis patients. Conclusion: Guided imagery has an effect on anxiety and pain in cholelithiasis patients at Sari Asih Hospital.